Anita Chan, Richard Madsen y Jonathan Unger. Chen Village under Mao and Deng. Berkeley: University of California Press. 2a. ed., aumentada y actualizada, 1992. 345 pp. - Connelly, Marisela (Estudios de Asia y África, 1994)
-